UV-radiation effects on photosynthesis, photosynthetic pigments and UV-absorbing substances in three species of tropical lotic macroalgae - Bautista-Saraiva, Anna Isabel N.; Bonomi-Barufi, Jose; Figueroa, Felix L.; Necchi, Orlando [UNESP] (Brazilian Soc Plant Physiology, 2018)
Freshwater algae inhabiting shallow waters are most effectively affected by UV radiation. The aim of this study was to analyze the photosynthetic performance (parameters derived of chlorophyll fluorescence), chlorophyll a concentrations and the content of UV-absorbing compounds (mycosporine-like aminoacids-MAAs) in three tropical lotic macroalgae, Cladophora glomerata (Chlorophyta), Spirogyra sp. (Streptophyta) and Sirodotia delicatula (Rhodophyta) in response to UV radiation exposure under laboratory conditions. Experiments were performed under three treatments: (1) PAR (400-700 nm), P; (2) PAR + UVA (320-700 nm), PA; (3) PAR + UVA + UVB (280-700 nm), PAB. Cladophora glomerata and Spirogyra sp., typical sun-adapted lotic macroalgae, had distinct responses to UV radiation exposure. A more pronounced decrease of F (v)/F (m) and increase of NPQ under UVA than UVAB was observed, whereas chlorophyll a content was lower under UVAB in C. glomerata. Spirogyra sp. had a decrease of photosynthetic yields (Delta F/F (m)' and F (v)/F (m)) under PAR, indicating that UVAB radiation may have a positive effect on the photosynthetic apparatus. Surprisingly, S. delicatula, a shade-adapted alga, exhibited less sensitivity to UV exposure. These results suggest that the presence of MAAs (shinorine and palythine) in S. delicatula is a significant shield of protection against UV radiation.
Keywords: Chlorophyll fluorescence; Green algae; Photosynthesis; Red algae; Radiation; UV-absorbing substances